Actors’ Roles in Citizen-driven Innovation - Sengewald, Timon; Roth, Angela (ISPIM Connects Osaka – Connecting and Empowering Society, 2024)
Amidst the global polycrisis, municipalities are urged to boost their resilience, with innovation playing a pivotal role in responding to challenges. Citizen-driven innovation has proven effective during the COVID-19 pandemic, with numerous solutions emerging from civic hackathons. However, while open innovation in businesses is well-researched, the dynamics of social and citizen- driven innovation remain less understood. Engaging civil society actors can advance municipal innovation and mitigate crises. This study, using a multiple case study approach with a qualitative content analysis of interviews and other available materials, aims to enhance our understanding of coordinating citizen- driven innovation and the interplay of different actor roles. By understanding the roles of actors and the unique aspects of social and public open innovation, municipalities can unlock the full potential of their citizens. This research offers insights to help cities harness the power of citizen-driven innovation more effectively.<br
Keywords: public open innovation; citizen-driven innovation; innovation actor roles

A Software Ecosystem for the Development of Digital Service Design Tools: A Conceptual Framework - Sengewald, Timon; Jalowski, Max; Schymanietz, Martin (Wirtschaftsinformatik 2021 Proceedings, 2021)
Numerous service design tools, techniques, and methods have been developed in science and practice alike (e.g., Persona, Service Blueprint, Stakeholder Map). Some of these tools build on each other, e.g., different developed Personas can be positioned and placed in a broader overall context within a Stakeholder Map. Digitisation of the design process can generate significant benefits; for instance, results can be transferred between different digital tools and devices using a common or standardised file format. However, there are few digital tools to support the service design process and most of them are not interoperable. This prevents the design of services using digital technologies from achieving their full benefits. To address this problem, an ecosystem is needed that can foster the development of digital-enabled service design tools. The paper follows a design science approach to create a framework involving five design objectives as necessary steps towards such a software ecosystem.
Keywords: service design; digital-enabled service design; service design tools; service innovation; design science research

A Taxonomy of Engagement Barriers for Municipal Climate Action Planning: Work in Progress - Sengewald, Timon; Posselt, Tim (Wirtschaftsinformatik 2022 Proceedings, 2022)
Sovereignty and equity-seeking groups are poorly engaged in municipal climate action planning due to various barriers. By using digital technologies, these barriers may be partly overcome. Due to the multitude of requirements regarding accessibility and simplicity, it is challenging to use or design a single application. Instead, a combination of multiple technologies can help overcome individual accessibility barriers and generate co-creative relationships across all stakeholder groups, allowing all groups to be involved in communication according to their accessibility needs. This study identifies design principles for such digital engagement tools and technologies to improve sovereignty- and equity-seeking groups' engagement within municipal climate action planning. It also provides a toolbox for municipalities to support the design of hybrid online-offline engagement systems with digital technologies. A design science research approach is used to develop a method for analyzing engagement systems.<br
Keywords: climate action planning; engagement barriers; sustainability justice; Chancengleichheit

A taxonomy of resident engagement barriers in public open innovation - Sengewald, Timon; Riemer, Manuel; Posselt, Tim (Ongoing Research, Practitioners, Posters, Workshops, and Projects at EGOV-CeDEM-ePart 2024, 2024)
As governments at different levels - federal, state, and local - face complex societal challenges such as climate change or the transformation towards smart cities, efforts to engage civil society in decision-making and planning processes are increasing. However, not all citizens/residents are equally involved and broad participation is sometimes absent. Two bodies of literature are especially relevant to understanding potential barriers to participation that can lead to inequitable involvement in digital public decision-making: citizen/resident participation and public open innovation. Both must consider the reasons why residents may be unaware, unwilling, or unable to participate and find new ways to approach them, especially those who are marginalized and historically underrepresented. To assist practitioners and scholars in categorizing existing knowledge on barriers, we used a design sciences research approach to create a taxonomy for classifying resident engagement barriers in public open innovation. The final taxonomy consists of two dimensions and 14 characteristics. Public sector professionals, consultants and academics can use this taxonomy as a shared language to identify potential barriers and improve their engagement with residents.
CRIS-Team Scopus Importer:2024-08-16
Keywords: citizen participation; public open innovation barriers; resident participation barriers

Designing an Engagement Platform for Municipal Climate Action Planning Addressing Equity and Justice - Sengewald, Timon (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2021)

Gestaltung von Benutzeroberflächen eines Artefakts zum Design von digitalisierten Service Systemen - Sengewald, Timon (2018)

How does the User Type Affect the Acceptance of Digital Innovation on the Job - Sengewald, Timon; Boha, Julian; Roth, Angela (Proceedings of the 2020 on Computers and People Research Conference, 2020)
Digital technologies promise greater effectiveness and higher productivity for companies. The question of the factors influencing the success of such technologies has long been a subject of research. However, these factors seem to be depending on the user type. This paper handles the case of the implementation of a new mobile application to support distinct work processes and presents preliminary results. A total of two field observations and 22 interviews were conducted to create a framework that promotes the development of digital innovations by systematically identifying characteristics that improve the adoption rate.<br

Identifying Customer Values of B2C-Fintech Services in the Area of Personal Financial Management - Busch, Jonas; Sengewald, Timon; Haag, Steffi (Wirtschaftsinformatik 2022 Proceedings, 2022)
Banksfacethechallengeofprovidingvaluethatconsumersarecom- fortable paying for. Although customer value is essential for fintech services, the scant research exclusively focuses on the technological advantages. This paper applies the Value-Focused-Thinking approach to identify which values fintech services regarding personal financial management (PFM) can create for customers. Through 24 qualitative interviews, we identify 14 fundamental objectives and 15 means objectives, which represent the potential customer values of PFM services (PFMS). The relationships of the identified objectives are illustrated in a Means- Objective-Network. We prioritized the identified values through a quantitative online survey with 167 potential customers. The results provide insights into the characteristics that PFMSs should have to achieve the highest possible value for customers. Customers see PFMS as valuable if they deem the service trustworthy and give them control over their finances. This paper provides an early exploratory research contribution about the customer values of PFMSs.
Keywords: Personal Financial Management; Fintech Services; Customer Values

Influence of Digital Open Innovation Platforms on Power Differentials within Municipalities - Sengewald, Timon; Posselt, Tim; Riemer, Manuel (SIGMIS-CPR 2024 - Proceedings of the Computers and People Research Conference: Trust and Legitimacy in Emerging Technologies: Organizational and Societal Implications for People, Places and Power, 2024)
Many municipalities are striving to increase citizen involvement in local decision-making processes, particularly those implementing smart city initiatives. These efforts often involve the introduction of digital open innovation platforms that invite residents to contribute ideas, co-create solutions, and participate in decision-making for urban innovations. However, it remains unclear whether the implementation of such platforms enhances the breadth and equity of social power among different resident groups. To address this issue, we adopted an explorative single case study design and conducted semi-structured interviews with 12 participants from the civic society and municipal administration to explore the power differentials created by the implementation of two digital OI platforms. Our findings provide critical insights into the impact of digital open innovation platforms on resident participation and the distribution of social power between different resident groups in the municipality, offering valuable guidelines for municipalities seeking to foster more inclusive and effective resident participation.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Digital open innovation platforms; Power differentials; Smart city; Smart municipality

SERVICE SYSTEMS ENGINEERING - Sengewald, Timon; Höckmayr, Benedikt; Roth, Angela; Hohmann, Christoph; Danzinger, Frank; Kalb, Dominik (2020)

Teaching AI Literacy for Innovation: Work in Progress - Sengewald, Timon; Tremmel, Agnes (SIGMIS-CPR 2024 - Proceedings of the Computers and People Research Conference: Trust and Legitimacy in Emerging Technologies: Organizational and Societal Implications for People, Places and Power, 2024)
This study addresses the question of how AI literacy could be taught in higher education institutions so that students acquire appropriate competences and skills that will later support them in using AI tools effectively in innovation processes. We used a design science approach to derive learning archetypes to design a corresponding course curriculum. To evaluate these learning archetypes, we had students work on innovation projects in a course and allowed students to use AI tools without restriction. However, the students were required to clearly state how they utilized the AI tools to produce their results. The results indicate that students who were deeply engaged with AI tools outperformed their peers. However, two groups of students were identified who would require different approaches in a course curriculum to potentially increase their AI literacy. While the first group of students underestimated the abilities of AI tools for their given task, the second group overestimated the results and was too early satisfied with them, lacking a certain amount of curiosity.
CRIS-Team Scopus Importer:2024-06-21
Keywords: AI literacy; AI-supported innovation; human-AI collaboration

The Contribution of International Students in Smart Cities Through Open Innovation - Wang, Wenwen; Sengewald, Timon (2024 Smart Cities Symposium Prague, SCSP 2024 - Proceedings, 2024)
The concept of the smart city has been an ongoing trend over the past two decades. Smart cities encourage citizen participation through innovative approaches to enhance urban resilience and sustainability. As a distinct aspect of the citizenship of a city, the contribution of international students to the smart city concept has not received enough attention. In this research, a qualitative study was conducted, involving 12 in-depth semi-structured interviews with international students across three different academic levels to investigate how the contribution to smart city innovation of international students can be enhanced. This study delves into the motivations, approaches, and potential barriers to their participation. The findings reveal that their involvement is mainly driven by addressing real-life problems and seeking recognition. An integrated approach through online platforms with in-person interactions could be helpful. However, to include them in the innovation process of smart cities, we must consider the unique difficulties they face.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Citizen Participation; International Students; Open Innovation; Smart City

User Experience of Creativity Support Tools – A Literature Review in a Management Context - Sengewald, Timon; Roth, Angela (15th International Conference on Wirtschaftsinformatik, 2020)
Creativity Support Tools or Creativity Support Systems are a well-studied subject in the research of computer science and information systems. Whether the User Experience of Creativity Support Tools or Creativity Support Systems has been likewise sufficiently researched, shall be examined. A systematic literature search was conducted to investigate the current state of scientific literature. This review provides a brief overview of open and superfluous research areas in the field of User Experience for the development of Creativity Support Tools for business or management purposes. A total of 19 papers were selected and coded, sorted to concepts and assigned to the various phases of the creative process. The results of the analysis have shown that there is a need for further research in this field.<br
Keywords: creativity support tools; creativity support systems; user experience

Who's got the power?: Examining the impact of digital open innovation platforms on social power dynamics in smart municipalities - Sengewald, Timon; Posselt, Tim; Riemer, Manuel (SIGMIS-CPR '23: Proceedings of the 2023 Computers and People Research Conference, 2024)
In the current efforts of many cities, towns, and regions to digitally transform into smart municipalities, there is a paradigm shift from mere resident participation to co-creation. In co-creation, residents and municipal staff form a unified workforce, working on digital innovations to improve the community's well-being and quality of life. However, the ability to use and access IT is not the same across all resident groups. This raises the question of how the design of digital open innovation platforms affects the power dynamics in collaboration between different resident groups. In this research-in-progress paper, we combine Work Systems Theory and Gaventa's "power cube" to form a theoretical framework that can be used to analyze the power dynamics between different resident groups. Our study aims to help researchers and practitioners design better digital open innovation platforms that can empower marginalized groups. A better balance of power can ensure that all members of the municipal community benefit and do not become further marginalized.<br